MALAYSIAN SCHOLARLY E-JOURNALS: FOCUS ON EJUM, A JOURNAL MANAGEMENT SYSTEM - A.N., Zainab; N.N., Edzan (Malaysian Journal of Library and Information Science, 2000)
Presents an overview of the various Malaysian scholarly electronic journals available on the Internet and describes the issues involved in setting up a journal hosting system which currently publishes the Malaysian Journal of Library & Information Science (MJLIS) and Malaysian Journal of Computer Science (MJCS). Both journals are accessible via the Internet in 1999 with its print equivalent still being published and distributed.